Application of Legal Culture to National Development - Fransisca Dewi Zion (International Journal Labs, 2023)
The evolution of Indonesia's cultural identity has undergone a profound transformation, impacting the nation's nature, personality, and overall identity. However, this transformation hasn't been fully paralleled in the development of the country's legal culture, which lags behind in comparison. This shift in legal culture can be attributed to a blend of internal and external factors. Internally, the moral fabric of the nation plays a pivotal role in shaping the legal culture. Externally, technological advancements and the influx of foreign ideas and cultures contribute significantly. These external influences are often rooted in globalization, which exposes the nation to diverse legal frameworks and ideologies. The state of the legal culture holds substantial sway over the nation's development, and its deficiency can lead to legal chaos. Legal culture isn't just a passive component; it actively participates in the formulation of laws and their subsequent enforcement. In essence, the collapse or inadequacy of the legal culture can exert detrimental effects on the progress of the legal system and, by extension, national development. Thus, fostering a robust and adaptable legal culture is imperative to navigate the complexities of modern society and ensure coherent legal development.